Shalat Practice: Practical Action Research Using the Demonstration Method in Children Aged 5-7 Years - Imam Tabroni; Susi Suaebah; Fildza Qanita Raihan; Zahro; Syifa Nurul Aini (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this action research is to improve the prayer ability of children aged 5-7 years. Prayer is a movement and reading that starts from takbiratul ihram and ends by saying greetings followed by the final movement of the prayer. Prayer readings: read the letter al-Fatihah, some letters of the Qur'an, tasbih, tahmid, tasyahud, and greetings. Prayer movements: takbir, standing, bowing, i`tidal, prostration, sitting between two prostrations, and sitting final tasyahud. The research was conducted at Baiturrahman DTA with an action research method using cycles: 1) looking at children's prayer abilities, 2) designing and preparing demonstration methods, 3) practicing prayers using demonstration methods. Data analysis before and after the action is used as the next cycle process. The cycle process ends with the meaning of the data. The results of the study showed an increase in the understanding and practice of good prayer. Movement and readings changed in three cycles. The first cycle is still not perfect in bowing and reading al-fatuhah. The second cycle is improved and the movement appears which is still not calm. In the third cycle perfected. The demonstration method has proven to be effective for carrying out practical actions in improving prayer practices at DTA Baeturrahman Maniis Purwakarta.